2018
DOI: 10.1038/s41416-018-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

The added value of genetic information in colorectal cancer risk prediction models: development and evaluation in the UK Biobank prospective cohort study

Abstract: Colorectal cancer (CRC) risk prediction models could be used to risk-stratify the population to provide individually tailored screening provision. Using participants from the UK Biobank prospective cohort study, we evaluated whether the addition of a genetic risk score (GRS) could improve the performance of two previously validated models. Inclusion of the GRS did not appreciably improve discrimination of either model, and led to substantial miscalibration. Following recalibration the discrimination did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…To gauge the potential public health impact of applying such risk prediction model in the general population, we estimated the 10-year absolute risk of the general UK population ( Figure S3, Most previous efforts mainly focused on the predictive ability of PRS to capture the overall risk of CRC. 4,5,[22][23][24] However, there is compelling evidence suggesting that genetic risk factors may differ by anatomic locations. 25 We therefore aimed to improve prediction of sitespecific CRC by deconstructing the commonly used genomic risk score into several regional scores, allowing susceptibility signals through multiple/different mechanisms to influence genetic predisposition to site-specific CRC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gauge the potential public health impact of applying such risk prediction model in the general population, we estimated the 10-year absolute risk of the general UK population ( Figure S3, Most previous efforts mainly focused on the predictive ability of PRS to capture the overall risk of CRC. 4,5,[22][23][24] However, there is compelling evidence suggesting that genetic risk factors may differ by anatomic locations. 25 We therefore aimed to improve prediction of sitespecific CRC by deconstructing the commonly used genomic risk score into several regional scores, allowing susceptibility signals through multiple/different mechanisms to influence genetic predisposition to site-specific CRC.…”
Section: Resultsmentioning
confidence: 99%
“…Hsu et al developed sex‐specific models by using family history and 27 common genetic variants with adjustment of endoscopy history and obtained a discrimination ability of 0.59 for men and 0.56 for women 22 . Similarly, Smith et al reported a c‐statistic of 0.57 for genetic risk model combing 41 CRC susceptibility SNPs 23 . The most recent genetic model for CRC was developed by Jeon et al including 63 CRC susceptibility SNPs and achieved a slightly improved predictive accuracy with a c‐statistic of 0.59 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous efforts mainly focused on the predictive ability of PRS to capture the overall risk of CRC. 5,6,[23][24][25] However, there is compelling evidence suggesting that genetic risk factors may differ by anatomic locations. 26,27 We therefore specifically aimed to improve prediction of site-specific CRC by deconstructing the commonly used genomic risk score into several regional scores, allowing susceptibility signals through multiple/different mechanisms to influence genetic predisposition to site-specific CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, risk stratification was not formally evaluated. Considering cancerspecific studies, the PRS presented here achieved superior prediction performance for some cancers 19,20,21,22 , but not others 23,24 . For pancreatic cancer 25 and melanoma 26 , our results are consistent with previous analyses using PRS of similar composition.…”
Section: Discussionmentioning
confidence: 87%